2021
DOI: 10.1142/s1793604721510437
|View full text |Cite
|
Sign up to set email alerts
|

A facile method for preparation of porous nitrogen-doped Ti3C2Tx MXene for highly responsive acetone detection at high temperature

Abstract: Porous nitrogen-doped Ti3C2T[Formula: see text] MXene (N-TCT) with a three-dimensional network structure is synthesized via a simple sacrifice template method and then utilized as an acetone gas sensor. By introducing nitrogen atoms as heteroatoms into Ti3C2T[Formula: see text] nanosheets, some defects generate around the doped nitrogen atoms, which can greatly improve the surface hydrophilicity and adsorption capacity of Ti3C2T[Formula: see text] Mxene nanosheets. It resulted in the enhanced gas sensitivity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Compositional modification on MXenes can be done not only by substituting one transition metal with another transition metal or by changing the composition of functional groups but also by doping elements with higher valence electrons as well as heavier metals. 115 As ferromagnetism in MXenes is mainly attributed to unpaired electrons of 3d orbitals of transition metals adjacent to the Fermi level, increasing the number of unpaired electrons will probably increase the magnetic properties. Furthermore, doping will change the electronic and magnetic properties of the materials.…”
Section: Tuning the Composition Of Mxenesmentioning
confidence: 99%
“…Compositional modification on MXenes can be done not only by substituting one transition metal with another transition metal or by changing the composition of functional groups but also by doping elements with higher valence electrons as well as heavier metals. 115 As ferromagnetism in MXenes is mainly attributed to unpaired electrons of 3d orbitals of transition metals adjacent to the Fermi level, increasing the number of unpaired electrons will probably increase the magnetic properties. Furthermore, doping will change the electronic and magnetic properties of the materials.…”
Section: Tuning the Composition Of Mxenesmentioning
confidence: 99%
“…KWO/Ti 3 C 2 T x showed the best response at a 2 : 1 ratio. Z. Wang et al 161 showed the porous nitrogen-doped Ti 3 C 2 T x used as an acetone gas sensor due to its three-dimensional structure, which was synthesized by the sacrificial template method. When heteroatoms such as nitrogen atoms are introduced into Ti 3 C 2 T x nanosheets, certain defects are produced throughout the nitrogen atoms, which can improve the hydrophilicity and adsorption characteristics of the Ti 3 C 2 T x nanosheet.…”
Section: Materials Advancesmentioning
confidence: 99%
“…Heterostructures-based MXenes were developed to enhance the gas sensing properties, and they benefit from a built-in Schottky junction and a charge-trapping mechanism [ 151 , 152 ]. Surface and structural engineering have been approved as alternative techniques to improve the gas sensing of MXenes towards VOCs [ 153 , 154 ]. Herein, we emphasize and provide the recent application of green MXenes for gas sensors.…”
Section: Potential Of Green Mxenes For Environmental Biomedical Elect...mentioning
confidence: 99%